Athletic shorts : six short stories - Crutcher, Chris (New York : HarperTempest, 2002)
A collection of short stories featuring characters from earlier books by Chris Crutcher.
A brief moment in the life of Angus Bethune -- The pin -- The other pin -- Goin' fishin' -- Telephone man -- In the time I get.
"A Greenwillow book.".
School Library Journal starred.
Wilson's Junior High School.
Wilson's Senior High School.
6.5
Young Adult
Keywords: Athletes -- Fiction; Short stories; Sports -- Fiction; Athletes -- Fiction; Short stories; Sports -- Fiction